The agricultural antibiotic carbadox induces phage-mediated gene transfer in Salmonella - Bearson, Bradley L.; Allen, Heather K.; Brunelle, Brian W.; Lee, In Soo; Casjens, Sherwood R.; Stanton, Thaddeus B. (Frontiers in Microbiology, 2014)
Antibiotics are used for disease therapeutic or preventative effects in humans and animals, as well as for enhanced feed conversion efficiency in livestock. Antibiotics can also cause undesirable effects in microbial populations, including selection for antibiotic resistance, enhanced pathogen invasion, and stimulation of horizontal gene transfer. Carbadox is a veterinary antibiotic used in the U.S. during the starter phase of swine production for improved feed efficiency and control of swine dysentery and bacterial swine enteritis. Carbadox has been shown in vitro to induce phage-encoded Shiga toxin in Shiga toxin-producing Escherichia coli and a phage-like element transferring antibiotic resistance genes in Brachyspira hyodysenteriae, but the effect of carbadox on prophages in other bacteria is unknown. This study examined carbadox exposure on prophage induction and genetic transfer in Salmonella enterica serovar Typhimurium, a human foodborne pathogen that frequently colonizes swine without causing disease. S. Typhimurium LT2 exposed to carbadox induced prophage production, resulting in bacterial cell lysis and release of virions that were visible by electron microscopy. Carbadox induction of phage-mediated gene transfer was confirmed by monitoring the transduction of a sodCIII::neo cassette in the Fels-1 prophage from LT2 to a recipient Salmonella strain. Furthermore, carbadox frequently induced generalized transducing phages in multidrug-resistant phage type DT104 and DT120 isolates, resulting in the transfer of chromosomal and plasmid DNA that included antibiotic resistance genes. Our research indicates that exposure of Salmonella to carbadox induces prophages that can transfer virulence and antibiotic resistance genes to susceptible bacterial hosts. Carbadox-induced, phage-mediated gene transfer could serve as a contributing factor in bacterial evolution during animal production, with prophages being a reservoir for bacterial fitness genes in the env